From the Anthropocene to the Machinocene ? - De Caro, Mario (Itinerari, 2023)
Is the Anthropocene near the end? Some reasons suggest that it may be so, because of the way machines – and especially intelligent machines – are dramatically changing our lives. Firstly, for the first time in history, new machines may be generating a dramatic increase in unemployment, which can cause severe economic and social problems. Secondly, human error or malice, applied to military or industrial machines can produce terrible consequences for humans and the natural environment. Thirdly, and more importantly, a time may come (the so-called “Singularity”) in which artificial intelligence may become uncontrollable and very dangerous for us. Against a common opinion according to which machines cannot do what we do not tell them to do, I will discuss a case in which machines are not just much better than us, but are already creative in ways that we cannot anticipate or even understand.